TRANSNATIONAL JUSTICE: IN SEARCH OF UNIVERSALIZATION OF RIGHTS - Tomaz, Roberto Epifanio (Unoesc International Legal Seminar, 2017)
This article is about understanding the universalization of the law as a way to realization of a Transnational Justice. The objective is to evaluate the Law and the phenomenon of transnationalization, borned in the context of globalization, as can limiting aspects of globalization’s hegemonic effects, and encouraging the emergence of a new political and legal order more just and humanitarian. The method used for the research was inductive; treatment data, was the cartesian, and the reporting of results found in this article, the logical base is also inductive, approach is descriptive, with analytical and prescriptive contributions. In order to offer support to the methods operation, the techniques employed were the referent, category, the operational concept and bibliographic and documentary research, the latter, by electronic means.